Relationship between preterm, low birth weight, and development defects of enamel in the primary dentition: A meta-analysis - Xu, Shan; Zhao, Caiyun; Jia, Liying; Ma, Zhe; Zhang, Xiaolin; Shi, Hong (Frontiers in Pediatrics, 2022)
Background: The purpose of this study was to systematically analyze the relationship between preterm (PT), low birth weight (LBW) and development defects of enamel (DDE) in the primary dentition. Methods: After the databases were retrieved, case-control studies, cross-sectional studies, and cohort studies about the relationship between PT, LBW and DDE, published in English or Chinese up to January 2022 were included. The data about odds ratio (OR) and 95% confidence interval (95% CI) were extracted and calculated with STATA 12.0 Software. Case-control studies were evaluated using the Newcastle-Ottawa Scale (NOS), whereas cross-sectional studies and cohort studies were evaluated using the JBI scale. The heterogeneity of each study was evaluated with the Q test. Results: A total of fifteen studies were included, of which eight studied the relationship between PT and DDE, and thirteen explored the relationship between LBW and DDE including three about the relationship between very low birth weight (VLBW) and DDE. There were seven studies that explored the relationship between PT, LBW and DDE. The results of this meta-analysis showed that both PT and LBW especially VLBW (OR =7.19, 95% CI: 4.98-10.38) were risk factors for DDE in the primary dentition (OR =2.33, 95% CI: 1.55-3.51) (OR =1.67, 95% CI: 1.08-2.59). The subgroup results showed that PT and LBW were both associated with the occurrence of enamel hypoplasia (EHP) (OR =6.89, 95% CI: 3.33-14.34) (OR =2.78, 95% CI: 2.10-3.68) rather than enamel opacity (OR =0.94, 95% CI: 0.55-1.61) (OR =1.03, 95% CI: 0.66-1.61). There was no publication bias about the included studies (P =0.75 >0.05) (P =0.47 >0.05). Conclusion: This meta-analysis demonstrated that both PT and LBW especially VLBW are associated with a higher risk of DDE in the primary dentition. PT and LBW are both related to the occurrence of EHP. However, the relationship between PT, LBW and enamel opacity has not been verified.